Bakre skallgropens form hos hund : en studie av occipital hypoplasi hos hund - Spångberg, Camilla (SLU/Dept. of Animal Environment and Health (until 231231), 2006)
Chiari type I malformation is a condition in humans characterized by a small posterior cranial fossa, downward herniation of the cerebellar tonsils, foramen magnum overcrowding and disturbances of cerebrospinal fluid dynamics. Syringohydromyelia is often seen in patients with Chiari type I malformation. Syringohydromyelia is characterized by fluid-filled cavities in the spinal cord. This causes damage to the nervous tissue in the spinal cord. In recent years, a condition similar to Chiari type I malformation has been recognized in dogs. It has mostly been seen in Cavalier King Charles spaniels (CKCS). The condition seen in dogs is usually called occipital bone hypoplasia.